Convergent phosphomodulation of the major neuronal dendritic potassium channel Kv4.2 by pituitary adenylate cyclase-activating polypeptide. (February 2016) - Gupte, Raeesa P.; Kadunganattil, Suraj; Shepherd, Andrew J.; Merrill, Ronald; Planer, William; Bruchas, Michael R.; Strack, Stefan; Mohapatra, Durga P.
Abstract: The endogenous neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) is secreted by both neuronal and non-neuronal cells in the brain and spinal cord, in response to pathological conditions such as stroke, seizures, chronic inflammatory and neuropathic pain. PACAP has been shown to exert various neuromodulatory and neuroprotective effects. However, direct influence of PACAP on the function of intrinsically excitable ion channels that are critical to both hyperexcitation as well as cell death, remain largely unexplored. The major dendritic K + channel Kv4.2 is a critical regulator of neuronal excitability, back-propagating action potentials in the dendrites, and modulation of synaptic inputs. We identified, cloned and characterized the downstream signaling originating from the activation of three PACAP receptor (PAC1) isoforms that are expressed in rodent hippocampal neurons that also exhibit abundant expression of Kv4.2 protein. Activation of PAC1 by PACAP leads to phosphorylation of Kv4.2 and downregulation of channel currents, which can be attenuated by inhibition of either PKA or ERK1/2 activity. Mechanistically, this dynamic downregulation of Kv4.2 function is a consequence of reduction in the density of surface channels, without any influence on the voltage-dependence of channel activation. Interestingly, PKA-induced effects on Kv4.2 were mediated by ERK1/2 phosphorylation of the channel at two critical residues, but not by direct channel phosphorylation by PKA, suggesting a convergent phosphomodulatory signaling cascade. Altogether, our findings suggest a novel GPCR-channel signaling crosstalk between PACAP/PAC1 and Kv4.2 channel in a manner that could lead to neuronal hyperexcitability. Graphical abstract: Highlights: PACAP activation of hippocampal PAC1 isoforms leads to PKA and ERK1/2 activation. The major dendritic K + channel Kv4.2 is dynamically downregulated by PAC1/PKA/ERK1/2 signaling. Convergence of PKA and ERK1/2, and phosphorylation of Kv4.2 by the later reduces channel density. PACAP modulation of Kv4.2 is not influenced by voltage-dependence of channel activation.